Residents’ perceptions of ecosystem services in an urbanizing basin: A case study in the Guanting Reservoir basin, China - Yansong Bai; Qingxu Huang; Luis Inostroza; Haoran Xu; Dan Yin; Ziwen Liu; Ling Zhang; Fangjin Xu (Geography and Sustainability, 2024)
Understanding stakeholders’ differences in perceptions of ecosystem services (ES) is crucial for guiding ecological conservation and planning. However, the variations of ES perception amongst different types of residents in urbanizing areas along an urban-rural gradient are still poorly understood. Combining a questionnaire-based survey, redundancy analysis, and statistical tests, we delineated the urban-rural gradient according to local residents’ socio-economic characteristics, and investigated the differences in local residents’ perceptions of ES and potential factors affecting them in the Guanting Reservoir basin, a rapidly urbanizing basin in China. The results showed that residents living in urban-rural transitional areas attached great importance to provisioning services of providing food and domestic water, regulating services of carbon sequestration and air purification, and cultural services of providing education and training, which were 0.7%–13.1%, 0.7%–9.1% and 2.5%–21.2% higher than that of residents in other areas, respectively. Age and occupation were major factors affecting residents’ perceptions. In terms of land-use types that deliver ES, the difference in perceptions of ES delivered by grassland was the greatest amongst residents. Our results support recommendations for policymakers to take into account the stakeholders’ diverse perceptions, thus promoting residents’ sense of gain on ES.